Hypertrophic pachymeningitis: a rare manifestation of IgG4 related disease - Sandeepan, Kumar; Jha, Monika; Purari, Shiv; Sharma, Pallav K.; ., Shreyash; Kumar, Chandan (International Journal of Research in Medical Sciences, 2023)
Hypertrophic pachymeningitis (HP) is a rare form of diffuse inflammatory disease that causes thickening of the dura mater. It can involve the cranial or the spinal dura or both. An increasingly well-known symptom of IgG4-related illness, a fibroinflammatory syndrome that may affect almost any organ, is IgG4-related hypertrophic pachymeningitis (IgG4-RHP). It is estimated that IgG4-RHP may account for a high proportion of cases of hypertrophic pachymeningitis once considered idiopathic. Contrast magnetic resonance imaging (MRI) shows pachymeningeal enhancement. Serum IgG4 levels may be elevated but are normal in most patients. However, most patients have elevated cerebrospinal fluid (CSF) IgG4 index. Hence, CSF IgG4 index could serve as a less invasive diagnostic marker of IgG4-RHP. Confirmation of diagnosis is by meningeal biopsy that shows swirling “storiform” fibrosis with lymphocytic infiltrates, obliterate phlebitis and IgG4 positive plasma cells. This case highlights the diagnostic dilemma of IgG4-RHP as gold standard of diagnosis is meningeal biopsy which has many of its own limitations. CSF IgG4 index could be an alternate option for meningeal biopsy when the procedure is contraindicated or uninformative.